1999
DOI: 10.1007/s002110050453
|View full text |Cite
|
Sign up to set email alerts
|

The modified method of characteristics with adjusted advection

Abstract: The MMOC procedure for approximating the solutions of transport-dominated diffusion problems does not automatically preserve integral conservation laws, leading to (mass) balance errors in many kinds of flow problems. The variant, called the MMOCAA, discussed herein preserves the conservation law at a minor additional computational cost. It is shown that its solution, in either Galerkin or finite difference form, converges at the same rates as were proved earlier by Douglas and Russell for the standard MMOC pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 10 publications
0
64
1
2
Order By: Relevance
“…The conventional MMC methods have been widely used to approximate the solution of (4.1), compare [4,9,8,16,24,26,30,29] for analysis and computational aspects of these methods for general transport-diffusion problems. As applied to (4.1), the MMC consists of an advective-diffusive splitting of the equations along the characteristics.…”
Section: Extension To Transport-diffusion Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional MMC methods have been widely used to approximate the solution of (4.1), compare [4,9,8,16,24,26,30,29] for analysis and computational aspects of these methods for general transport-diffusion problems. As applied to (4.1), the MMC consists of an advective-diffusive splitting of the equations along the characteristics.…”
Section: Extension To Transport-diffusion Problemsmentioning
confidence: 99%
“…In addition, it has been observed that the error of the conventional MMC in solving advectiondiffusion problems decreases as the time step increases in a certain range of parameters. Analysis of the convergence and stability of the conventional MMC has been carried out in many papers, among others, in [4,8,9,24,33]. For convection-dominated equations with a diffusion bounded away from zero, the authors of [9] show an optimal error estimate…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the derived error estimate suffers from the same limitation as the earlier error estimates for many other characteristic methods, e.g. the modified method of characteristics (MMOC) [6], the modified method of characteristics with adjusted advection (MMOCAA) [7], and the Eulerian-Lagrangian localized adjoint method (ELLAM) for unsteady-state advection-diffusion equations with general boundary conditions [8]. Namely, the generic constant in the estimates may depend inversely on the vanishing diffusion parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Among them the procedure of the characteristic method is natural from the physical point of view since it approximates particle movements, and it is attractive from the mathematical point of view since it symmetrizes the problem. Many authors have contributed to develop, analyse and apply characteristic finite element schemes; see [1], [4], [6], [7], [8], [13], [14], [15], [16], [21] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of characteristic methods it it not trivial to maintain this property. Some schemes have been proposed and studied from this point [1], [6], [8], [21].…”
Section: Introductionmentioning
confidence: 99%